Happiness in the Psalms - Gordon McConville (Acta Theologica)
The article enquires into the nature of happiness or well-being in the Old Testament Psalms. It considers first the Psalms’ use of ‘happiness’ language, then goes on to seek a broader basis for the enquiry in key concepts such as freedom and justice, making some comparisons with Greek ideas. Finally it seeks to build up a picture of the person at the centre of the Psalms, particularly as the one who speaks, chiefly from the perspectives of speech itself, the ‘soul’, and praise, in the expectation that this may provide a portrait of the fulfilled human being.